Semi-arid zone caves: Evaporation and hydrological controls on δ18O drip water composition and implications for speleothem paleoclimate reconstructions. (1st January 2016) - Markowska, Monika; Baker, Andy; Andersen, Martin S.; Jex, Catherine N.; Cuthbert, Mark O.; Rau, Gabriel C.; Graham, Peter W.; Rutlidge, Helen; Mariethoz, Gregoire; Marjo, Christopher E.; Treble, Pauline C.; Edwards, Nerilee
Abstract: Oxygen isotope ratios in speleothems may be affected by external processes that are independent of climate, such as karst hydrology and kinetic fractionation. Consequently, there has been a shift towards characterising and understanding these processes through cave monitoring studies, particularly focussing on temperate zones where precipitation exceeds evapotranspiration. Here, we investigate oxygen isotope systematics at Wellington Caves in semi-arid, SE Australia, where evapotranspiration exceeds precipitation. We use a novel D2 O isotopic tracer in a series of artificial irrigations, supplemented by pre-irrigation data comprised four years of drip monitoring and three years of stable isotope analysis of both drip waters and rainfall. This study reveals that: (1) evaporative processes in the unsaturated zone dominate the isotopic composition of drip waters; (2) significant soil zone 'wetting up' is required to overcome soil moisture deficits in order to achieve infiltration, which is highly dependent on antecedent hydro-climatic conditions; (3) lateral flow, preferential flow and sorption in the soil zone are important in redistributing subsurface zone water; (4) isotopic breakthrough curves suggest clear evidence of piston-flow at some drip sites where an older front of water discharged prior to artificial irrigation water; and (5) water residence times in a shallow vadose zone (<2 m) are highly variable and can exceed six months. Oxygen isotope speleothem records from semi-arid regions are therefore more likely to contain archives of alternating paleo-aridity and paleo-recharge, rather than paleo-rainfall e.g. the amount effect or mean annual. Speleothem-forming drip waters will be dominated by evaporative enrichment, up to ∼3‰ in the context of this study, relative to precipitation-weighted mean annual rainfall. The oxygen isotope variability of such coeval records may further be influenced by flow path and storage in the unsaturated zone that is not only drip specific but also influenced by internal cave climatic conditions, which may vary spatially in the cave. Highlights: Subsurface evaporation drives drip water isotopic composition in semi-arid karst. Semi-arid zone speleothem δ 18 O records recharge frequency not rainfall composition. Dry antecedent conditions increases spatiotemporal variability in drip water δ 18 O. Weaker replication of semi-arid zone speleothem δ 18 O records is expected.